Methods for Ranking Sports Teams - Palionis, Eimantas; Chadyšas, Viktoras (Lithuanian Journal of Statistics, 2015)
The paper describes various methods that can be applied to the ranking of sports teams. Using the real data of theNational Basketball Association (NBA) from the first half of the 2014–2015 season (from 2014-10-28 to 2015-02-12), teams areranked using different ranking methods. All methods are compared with each other.
Keywords: sports teams ranks; ranking methods; ranking list